1989
DOI: 10.2135/cropsci1989.0011183x002900050038x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Influence on Susceptibility of Bermudagrass to Helminthosporium cynodontis Toxin

Abstract: Inadequate K fertilization of bermudagrass, Cynodon dactylon (L.) Pers., can lead to stand loss and increased disease symptoms. This study was conducted to determine the relationship between fungal leaf spot (Helminthosporium cynodontis Marig.) susceptibility and K status of hybrid bermudagrass ‘Grazer’ and ‘Tifton 78’ bermudagrass were grown in washed sand under six K fertilization rates (10, 30, 70, 100, 200, and 400 mg kg−1) in a greenhouse. Plants were clipped three times at 28‐d intervals and the K concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…Forage crops require similar amounts of K as N. Low K availability is often associated with stand mortality and increased incidence of pest and diseases (Matocha and Smith, 1980; Richardson and Croughan, 1989). Intensively managed hay production systems require application of K removed in the forage to sustain crop yields.…”
Section: Phosphorus and Potassium Fertilizationmentioning
confidence: 99%
“…Forage crops require similar amounts of K as N. Low K availability is often associated with stand mortality and increased incidence of pest and diseases (Matocha and Smith, 1980; Richardson and Croughan, 1989). Intensively managed hay production systems require application of K removed in the forage to sustain crop yields.…”
Section: Phosphorus and Potassium Fertilizationmentioning
confidence: 99%
“…Likewise, soil-test K in September 2009 was lower in plots previously fertilized with 9 than 18 Mg litter/ha (30 vs. 38 mg/kg, P < 0.05). These levels of soil K, which are categorized in the very low or low indices based on five southern states that employ the Mehlich-3 extractant (19), strongly suggest rapid annual changes in soil K influenced bermudagrass K nutrition and hence, its susceptibility to fungal diseases (1,15). Indeed, during 2 years of ryegrass-bermudagrass hay production the levels of soil K decreased progressively from approximately 108 mg/kg in September of 2007 to approximately 42 mg/kg in April of 2009 and to 34 mg/kg in September of 2009 ( Fig.…”
Section: Experimental Design Site History and Application Of Treatmmentioning
confidence: 99%
“…They reported an inverse, curvilinear relationship between tissue K and disease severity, and a large decrease in severity between 0 and 112 kg K/ha with slight or no decrease in the disease when tissue K levels exceeded approximately 8.0 g/kg. In a similar greenhouse trial, bermudagrass was grown using six K fertilization rates, sprayed with a culture filtrate of B. cynodontis , and evaluated for leaf necrosis caused by a toxin (15). These authors also observed a curvilinear relationship between severity of symptoms and tissue K levels, and they identified a threshold level of K for reduction in symptoms of approximately 25 g/kg, as well as cultivar differences in disease severity at similar levels of tissue K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O cálcio aumenta a resistência à doenças provavelmente devido ao seu efeito na composição da parede celular, tomando-a mais resistente à penetração por patógenos (Agrios, 1988 , indicando que a análise de tecido e fertilização potássica adequada podem ser usadas como prevenção para reduzir problemas com doenças em grama bermuda. Matocha & Smith (1980) também observaram, em condições de campo, relação entre a severidade de mancha foliar e o nível de K no tecido de grama bermuda Coastal (C. dacty/on), porém o nível crítico de K no tecido foi 6 g kg-\ inferior ao observado por Richardson & Croughan (1989).…”
Section: Mancha Foliar (Helminthosporium)unclassified